ระบบแสดงผลการตรวจจับสัญญาณคลื่นไฟฟ้าหัวใจด้วยคอมพิวเตอร์บอร์ดเดี่ยว: An ECG Detection and Display System with Single-board Computer - Buranapanichkit, Dujdow; Chanchaichujit, Pongsakorn; Chairat, Waranya (Journal of Science and Technology Songkhla Rajabhat University, 2025)
Currently, cardiovascular diseases are one of the leading causes of death in Thailand, particularly coronary artery diseases or heart blockages. Major risk factors include unhealthy dietary habits, insufficient physical activity, stress, and genetic predisposition, all of which negatively affect heart health. One of the most effective ways to reduce the risk and prevent fatalities from cardiovascular diseases is electrocardiogram (ECG) screening. An ECG can help detect heart abnormalities at an early stage, allowing for the prevention of severe conditions and a reduction in mortality rates. Additionally, it plays a crucial role in diagnosing other heart diseases, enabling timely medical intervention and treatment. This research focuses on ECG screening using a single-board computer. The ECG signals are recorded through the data acquisition module, and the data is converted from analog to digital. The processing unit displays the signals in real-time through a GUI screen. It also shows some information that is useful for preliminary ECG signal analysis. The main advantage of this system is that it is affordable technology that incorporates modern technology, capable of detecting and recording ECG results without the need for an expensive ECG machine.